WANITA (NYAIE) DALAM NOVEL BUNGA ROOS DARI CIKEMBANG KARYA KWEE TEK HOAY - Septiani, Nur Alifah; Pramono, Dedi (Universitas Ahmad Dahlan, 2022)
Over 90 years (1870-1960), 800 authors published 3000 Chinese Malay erudite workshops. Bunga Roos from Cikembang is one of the most well-known workshops. The work was written by Kwee Tek Hoay, one of the most prolific authors of his day. Bunga Roos from Cikembang, similar to the previous Chinese Malay literary work, casts an indigenous womanish figure as a Chinese man's